Język ideologii a język agresji w wypowiedziach politycznych - Laskowska, Elżbieta (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
The writer works on the assumption that each linguistic statement interprets reality. Evaluation is a particular form of interpretation. Some statements assign value from the point of view of an adopted ideology. The writer applies A. Heywood’s understanding of ideology and various ideologies. The language of ideology is sometimes accompanied in public discourse by the language of aggression, which expresses negative emotions and, unlike the language of criticism, discredits an individual. On the basis of public statements quoted by the writer, she tries to demonstrate that the language of ideology does not necessarily have to be that of aggression, and that aggression does not have to be inspired by ideological differences between the speaker and the person subjected to aggression.